Trunk Neural Crest Migratory Position and Asymmetric Division Predict Terminal Differentiation - Alhashem, Zain; Camargo-Sosa, Karen; Kelsh, Robert N.; Linker, Claudia (Frontiers in Cell and Developmental Biology, 2022)
The generation of complex structures during embryogenesis requires the controlled migration and differentiation of cells from distant origins. How migration and differentiation are coordinated and impact each other to form functional structures is not fully understood. Neural crest cells migrate extensively giving rise to many cell types. In the trunk, neural crest cells migrate collectively forming chains comprised of cells with distinct migratory identities: one leader cell at the front of the group directs migration, while followers track the leader forming the body of the chain. Herein we analysed the relationship between trunk neural crest migratory identity and terminal differentiation. We found that trunk neural crest migration and fate allocation is coherent. Leader cells that initiate movement give rise to the most distal derivativities. Interestingly, the asymmetric division of leaders separates migratory identity and fate. The distal daughter cell retains the leader identity and clonally forms the Sympathetic Ganglia. The proximal sibling migrates as a follower and gives rise to Schwann cells. The sympathetic neuron transcription factor phox2bb is strongly expressed by leaders from early stages of migration, suggesting that specification and migration occur concomitantly and in coordination. Followers divide symmetrically and their fate correlates with their position in the chain.